CLASS TOGETHER IN REALIZING THE VALUES OF MODERATION OF ISLAMIC EDUCATION THROUGH MULTICULTURAL SCHOOL CULTURE - Firmansyah Firmansyah (International Journal Education Multicultural of Islamic Society, 2022)
Sultan Iskandar Muda High School in Medan under the auspices of The Sultan Iskandar Muda College Foundation located on Tengku Amir Hamzah Pekan I Sunggal Street, Medan Sunggal District, Medan Municipality. Sultan Iskandar Muda High School has its own uniqueness such as 1) Religion:religions recognized by the government such as Islam, Christianity, Buddhism, and Hinduism are in this school, Furthermore, mosques, churches, temples, and temples are built permanently in this school. 2)  Culture:the diversity oflanguages, traditions, values, beliefs, myths, norms, and various tribes such as batak, Javanese, Chinese, Tamil, Mandailing, Malay, Karo, Aceh, Padang, Nias, Sunda, Banten Palembang, Ambon and Pakistan are in this school.  This study aims  first:  to describe the values of moderation of Islamic education through multicultural school culture. This study uses qualitative type with Crasswell realist ethnography approach. Data collection techniques with participant observation techniques, in-depth interviews, and documentation. The result of this study is a joint class embodying the values of moderation of Islamic education through the culture of multicultural schools at SMA Sultan Iskandar Muda the first open values, secondly the value of dialogue, the third tolerance and the fourth is not extreme in religion.Keywords:  tolerance, dialogue, open and not extreme in religion